Gambaran Proses Penerimaan Diri Ibu yang Memiliki Anak Disleksia - Ganesia Devina; Handayani Penny (The Center for Disability Studies and Services Brawijaya University, 2016)
This research is intended in order to picture the process of self acceptance of the mothers whom their kids suffered dyslexia. This research uses quality approach with deep interview style. These data is gathered and done within three participants with the span of age between 20 to 40 years old who raises kids with dyslexia that ages between 7 to 11 years old, and has been diagnosed by certain psychologist. The interview is also done to two supporting participants that is significant others from the main participant. The result of the research shows that the psychological dynamics that occurred in the acceptance process is vary, include denial, anger, bargaining, depression, and acceptance. The dominant phase that is experienced by the participants is anger and depression. Self acceptance process is supported by factors that is mentioned by Hurlock. Beside that, these factors that is mentioned by Hurlock is also slows down the self acceptance process. This discussion is also discuss another factor that is affecting the self acceptance itself like education, social economic status, and social support.